Rezension von: Brunner, Karl; Jaritz, Gerhard, Landherr, Bauer, Ackerknecht - Frank, Jakob Rudolf (Württembergisch Franken, 1988)
Karl Brunner; Gerhard Jaritz: Landherr, Bauer, Ackerknecht. Der Bauer im Mittelalter: Klischee und Wirklichkeit. Wien u.a.: Böhlau 1985. 144 S.. Abb.